Dogen: Japan’s Original Zen Teacher - Liao, Lillian (Canadian Journal of Buddhist Studies, 2023)
STEVEN HEINE, Dogen: Japan’s Original Zen Teacher. Boulder, Colorado: Shambhala Publications, 2021. XXIII, 333 pp. CAN $39.95. ISBN 978-1-61180-980-0.,